Proactive personality and work engagement: the mediating role of thriving at work - Fahd, Mohammad (2020)
There are several factors in general which contribute towards the success of an organization in the current competitive market, but main source behind the continuous success of the organizations is workforce. Almost every successful organization consider their employees as an asset to the company, as they play vital role in success. However, to achieve the success employees need to have optimistic mind set, creative, energized, and engaged in their work. Similarly, many earlier studies have shown that employees with proactive personality are energized towards engaging in their work, but less attention given towards the concept of how proactive employees engage. Therefore, this research analyses the mediating effect of thriving at work in connecting the proactive personality with work engagement. Henceforth, a survey was conducted among the 160 full-time young Gen Y employees from the various industries covering middle East, Asia Pacific, Europe, Africa, and USA. The participants involved were represented all levels of the management i.e. Senior management, middle management, junior management, rank and file. Moving on, the result showed that the thriving at work mediates the relationship among proactive personality and work engagement. As proactive personality was found to be directly related to thriving at work and work engagement. Similarly, thriving was found to be positively related to work engagement. Finally, this study concluded that Gen Y employees contain proactive personality, will also thrive and get engaged in their work, when their job expectations are met by the organizations.